Iowa Birdline update, June 3, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for June 3, 1991. Highlights include the conclusion of the spring migration except for many shorebirds, White-rumped Sandpipers in particular. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed